The middle-income trap and the manufacturing transformation of the People's Republic of China (PRC): Asian experience and the PRC's industrial policy orientation - Qunhui Huang; Gang Liu; Jun He; Feitao Jiang; Yanghua Huang (Asian Development Bank Institute (ADBI), 2017)
The People's Republic of China (PRC) has been undergoing marvelous industrialization and manufacturing development in the past decades, which has promoted its fast economic growth and has reached a level of middle-income in recent years. It is widely accepted that the PRC's status as the "world's factory" has roots in its comparative advantage of cheap factors and production. As the PRC becomes a middle-income economy, the established development pattern of manufacturing needs to be transformed. This paper investigates the experience of high-income Asian economies with a focus on the size and productivity of manufacturing, when they were in and out of the middle-income stages. We find that (1) the share of manufacturing value added in GDP of those selected economies, at a constant price, keeps on increasing as per capita income grows, which is different from the trend of secondary industry as proposed by the Petty-Clark Theorem; (2) besides the relative size, the drastic improvement in the productivity of manufacturing by industrial restructuring is also prominent. The PRC is facing the risk of "premature deindustrialization" because of declining industrial share and growth rate of productivity, which are potentially weakening the PRC's capability to avoid the middle-income trap. The PRC needs to reinvent its industrial policy by adjusting its policy focus, optimizing policy formulation and implementation, and adopting more policy measures to boost manufacturing productivity.
Keywords: O14; N15; L16; O25; 330; Economics; Industry and trade